Technical factors affecting cardiac surgical mortality in Australia. (July 2019) - Chan, Justin CY; Gupta, Aashray K; Babidge, Wendy J; Worthington, Michael G; Maddern, Guy J
Aim: Examination of potentially avoidable issues in surgical deaths can provide a basis for quality improvement. Perioperative technical factors in cardiac surgery may lead or contribute to patient mortality. Using data from a well-established and comprehensive national surgical mortality audit, we aimed to identify and describe clinical management issues leading to mortality in Australian cardiac surgical patients. Methods: Retrospective analysis of a cardiac surgical dataset from the Australian and New Zealand Audit of Surgical Mortality (February 2009 to December 2015) was undertaken. Clinical management issues related to technical factors were analyzed using a thematic analysis approach. Technical clinical management issues were categorized based on the most common themes, followed by qualitative analysis of each theme. Results: We identified 256 patients with least one technical management issues (total 270). Injury to structures was the most common theme ( n  = 115, 44.9%), followed by unaddressed surgical pathology ( n  = 39, 15.2%) and inadequate myocardial protection ( n  = 34, 13.2%). More specifically, the most common structural injury involved the right ventricle, with the aorta and femoral vessels also commonly injured. The most common unaddressed surgical pathology was incomplete coronary revascularization, followed by systolic anterior motion of the mitral valve during mitral repair. Graft failure occurred during coronary artery bypass graft surgery, with a poor target vessel being a common issue. Conclusion: Technical factors in cardiac surgery resulting in potentially avoidable mortality constitute an important subset of deaths. These findings can inform various stakeholders to improve the quality and safety of surgical care.